The in-vitro and in vivo evaluations of orthopedic metal implant coated with silver composite: Potential treatment modality for implant related infection - Mohd Jan, Nurul Hafiza; Zulkifly, Ahmad Hafiz; Ibrahim, Mohd Zulfadzli; Sha'ban, Munirah; Mohd Toff, Mohd Radzi (Elsevier, 2019)
The prevalence of implant associated with infection remains high. The management of this incidence poses a major challenge in orthopedic field. Colonization of bacterial and biofilm adhesion on implant may lead to infection at underlying bone and surrounding tissues. The infection risks may be overcome by application of orthopaedic metallic implant coated with silver composite (OMICS) as alternative treatment of implant-infection related. The aimed of these studies were to evaluate the potential effect of orthopedic metal implant (plate) coated with silver composite through in vitro and in vivo experimental settings. Antimicrobial test through in vitro analysis indicated that OMICS showed excellent response of antibacterial agent against Staphylococcus aureus. The effects of OMICS on open fracture related with infection were assessed in New Zealand White Rabbit models. All rabbits were implanted with OMICS after six hours of tibial bone exposure. The implanted tibia was excised en bloc and evaluated by means of microbial assessments, radiography evaluation, gross inspection and histological analysis for any infection effects. After 3 weeks of implantation, microbial analysis revealed fewer colonies were noted at study group compared to control. By combining the radiograph, gross and histological data collected during the experimental follow up, there is no periosteal reaction noted at the surrounding on implanted area. The outcome of this study revealed positive response of the silver as antibacterial agent. These studies indicated that silver has antibacterial properties. In conclusion, these values suggested that orthopaedic metal implant coated with silver composite may have the potential to prevent implant related infections.